The serotonin transporter (5-HTTLPR) but not serotonin receptor (5-HT2C Cys23Ser) variant is associated with bipolar I disorder in Kurdish population from Western Iran. (17th March 2015) - Mohammadi, Sahar; Khazaie, Habibolah; Rahimi, Ziba; Vaisi-Raygani, Asad; Zargooshi, Newsha; Rahimi, Zohreh
Highlights: The SS genotype of 5-HTTLPR was associated with 1.79-fold increased risk of BID. The S allele increased the risk of adult-onset BID by 1.76-fold. 5-HT2C Cys/Ser polymorphism was not linked to the risk of BID. 5-HTTLPR and 5-HT2C polymorphisms were not associated with suicidal attempt. Abstract: The role of 5-HTTLPR and 5-HT2C Cys23Ser polymorphisms in the psychopathology of mood disorders and suicide behavior is controversial. The aim of present study was to investigate the association between 5-HTTLPR and 5-HT2C Cys23Ser variants and susceptibility to bipolar I disorder (BID). The 5-HT2C genotypes were studied in 152 patients with BID and 173 gender- and age-matched healthy individuals with Kurds ethnic background from Western Iran using PCR and PCR–RFLP methods. In recessive model (SS vs. LL + LS) the SS genotype was associated with 1.79-fold increased risk of BID ( p = 0.018). Also, the presence of S allele increased the risk of adult-onset BID by 1.76-fold ( p = 0.027). No association was detected between 5-HTTLPR genotypes and alleles with suicide attempt. The frequency of 5-HT2C Ser allele in patients and controls were 12.3 and 12.5%, respectively. Mutant allele of HT2C Ser had higher frequency in female (14.7%) than male (10.5%, p = 0.27) patients. The frequency of HT2C Ser allele in patients with a family history of BID tended to be higher (15.7%) than those without a family history of the disease (11.8%). The frequency of HT2C Ser allele in suicide attempter women was higher (16.7%) than those without a suicide attempt (14.3%). Our findings demonstrate 5-HTTLPR polymorphism might be a risk factor for BID and adult-onset BID in Kurds population. However, we found the lack of an association between 5-HT2C Cys/Ser variants and the risk of BID.